Strengthening Character and Legal Education with Pancasila Values in The School Environment - Permata, Chusnul Qotimah Nita; Rosida, Heni; Rastini, Rastini; Sanjaya, Jaka Bangkit; Adiyatma, Septhian Eka; Arifin, Ridwan (The Indonesian Journal of International Clinical Legal Education, 2022)
Character becomes the identity of a nation, establishing Pancasila as an ideological foundation. Implicitly states that Indonesia is a nation that places customary values, cultural values, and religious values at the top of the legal hierarchy. Strengthening Character Education is the government's effort to pay attention that character education is important to highlight. Using a literature review research method and comparing it with people's behavior in welcoming the times. As well as focusing on implementing the practice of Pancasila using examples of problems from each subject. The influence of foreign cultures makes moral degradation and it seems that Indonesia has lost its identity. So the formation of national character through practice and implementation taught in elementary schools is the best solution in strengthening the foundation, using the educational concept of Thomas Lickona ideas can be a consideration for the government that the contribution of Pancasila education through a personal approach and involving parents in shaping the character of their children. It is hoped that the correlation between knowledge and technology combined with etchial human beings will be able to make Indonesia a developed nation, and have ethical human resources.